Application of Gamma Radiation in Food, Medical Products and Agriculture - Klemo, Marsida; Dodbiba, Andon; Ylli, Arjana (Richtmann Publishing, 2012)
Sterilization of health care products, reduction of total microbial load in feed and food samples, extension of shelf-life of freshvegetables and genetic improvement of some plants are some of applications in the GU-3 gamma irradiation facility. The dosimetricsystem used is treated in this paper because dose and its uniformity are very important parameters of the radiation processing. They arerelated with chemical, biological and other physical changes in the irradiated product. To provide good dose uniformity (determined asthe ratio of maximal dose to minimal dose) it is applied the radiation technique based on the rotation of the vessel with the material insideit. The dose uniformity was about 105 %. With regard to reducing total microbial load in food and feed samples it was seen that thisquantity was reduced from )/g for control, up to >10/g for the irradiated samples. Over analytical controlof the irradiated health care products was confirmed their sterility. Irradiated fresh vegetables (tomato and strawberry) had a longer shelflifethan control. We used mutation breeding in pepper through radiation to improve crops quality and in M1 generation photosyntheticpigments were higher in mutant materials than control.